Edukasi manajemen kesehatan mental selama pandemi covid-19 - AKHMAD AZMIARDI; Iik Sartika; Budi Rahardjo; Hanifah Dina Aulia (ARKA INSTITUTE, 2022)
Covid-19 is a disease caused by the SARS-CoV-2 virus and is currently a worldwide pandemic. Pandemic conditions like this have an impact not only on physical health, but can also affect mental health. People feel fear and concern about personal safety. Pandemic conditions like this also have adverse consequences such as layoffs and unemployment which can lead to mental health problems such as stress. Objective: This community service aimed to increase knowledge and skills in maintaining mental health, especially during the Covid-19 pandemic.This community service activity is carried out in 3 stages, namely socialization and mental health education to members of the Village Health Forum (FKD), program formation and the third is program implementation for ±3 months. There was an increase in participants' knowledge after socialization and education and it was statistically significant (p<0.001). The formation of the